Electroacupuncture pre-treatment alleviates sepsis-induced cardiac inflammation and dysfunction by inhibiting the calpain-2/STAT3 pathway - Li, Xuqing; Wang, Li; Ying, Xinwang; Zheng, Yujun; Tan, Qianqian; Yu, Xiaolan; Gong, Jiahong; Li, Ming; Deng, Xiaofeng; Yang, Guanhu; Li, Shengcun; Jiang, Songhe (Frontiers in Physiology, 2022)
Electroacupuncture (EA) has both anti-inflammatory and cardio-protective effects. Activation of calpain pathway is involved in inflammation-associated diseases. In sepsis, the role of calpain-2-regulated STAT3 in cardio-protective mechanism of EA remains unclear. In this study, we aimed to elucidate the mechanism by which EA reduces cardiac inflammation and improves cardiac function during sepsis. EA pretreatment for seven days was applied in septic cardiomyopathy model induced by lipopolysaccharide (LPS). LPS-induced sepsis was associated with a dramatically systemic inflammation and cardiac dysfunction, which was alleviated by EA pre-treatment. LPS resulted in increases of inflammatory TNF-α and IL-1β via activation of calpain-2/STAT3 pathway. EA pre-treatment inhibited LPS-induced activation of cardiac calpain-2/STAT3 signalling. Additionally, inhibition of calpain-2 expression using the corresponding siRNA decreased the activities of STAT3 and pro-inflammatory factors in cardiomyocytes with LPS-treatment, confirming that LPS induced cardiac inflammatory responses via calpain-2/STAT3 pathway. Furthermore, suppression of STAT3 signalling enhanced anti-inflammatory effects of EA. These findings reveal mechanisms of EA protection against cardiac inflammation in sepsis via calpain-2/STAT3 pathway and may provide novel targets for clinical treatments of the sepsis-induced cardiac dysfunction.